Perioperacinė skysčių terapija: senos problemos, nauji sprendimai - Audrius Andrijauskas; Indrė Sakavičiūtė; Juozas Ivaškevičius; Narūnas Porvaneckas; Giedrius Kvederas; Darius Činčikas; Justas Mažunaitis; Ugnė Marmaitė; Lina Sakalaitė; Povilas Andrijauskas; Gerda Sakalauskaitė (Lietuvos Chirurgija, 2012)
Audrius Andrijauskas1, Indrė Sakavičiūtė2, Juozas Ivaškevičius1, Narūnas Porvaneckas3, Giedrius Kvederas2, Darius Činčikas1, Justas Mažunaitis2, Ugnė Marmaitė4, Lina Sakalaitė4, Povilas Andrijauskas4, Gerda Sakalauskaitė2